2010
DOI: 10.1111/j.1365-2966.2010.16724.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the effects of geometry and rotation on pulsar intensity profiles

Abstract: We have developed a method to compute the possible distribution of radio emission regions in a typical pulsar magnetosphere, taking into account the viewing geometry and rotational effects of the neutron star. Our method can estimate the emission altitude and the radius of curvature of particle trajectory as a function of rotation phase for a given inclination angle, impact angle, spin period, Lorentz factor, field line constant and the observation frequency. Further, using curvature radiation as the basic emi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Let L represent the line whose footpoint has the smaller colatitude. For a dipolar field, one expects from geometric arguments (neglecting rotation effects on curvature, as discussed in Gangadhara 2007 andThomas et al 2010) that the lower frequency emission will be observed from L and the higher frequency emission from H, and that the emission occurs at a greater altitude for L than for H. From Eq. (15),…”
Section: Generalisation For Ar Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Let L represent the line whose footpoint has the smaller colatitude. For a dipolar field, one expects from geometric arguments (neglecting rotation effects on curvature, as discussed in Gangadhara 2007 andThomas et al 2010) that the lower frequency emission will be observed from L and the higher frequency emission from H, and that the emission occurs at a greater altitude for L than for H. From Eq. (15),…”
Section: Generalisation For Ar Effectsmentioning
confidence: 99%
“…Note that although the direction of the subpulse phase track shift is fixed by the carousel geometry, the magnitude of the shift depends on r , which may well be a strong function of pulse phase (e.g. Gangadhara 2004;Thomas et al 2010). This can introduce further distortions in the shape of the subpulse phase track as it appears at different frequencies.…”
Section: Generalisation For Ar Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the observed emission pattern for curvature radiation from a single particle can be calculated, and scaled up by the square of the local plasma density at each emission site. Thomas et al (2010) describe one possible method for doing such a calculation, although it should be noted that they incorporate the phase-shifting effects of aberration and retardation post hoc. To our knowledge, no similar method exists for estimating intensity profiles assuming other possible mechanisms, such as maser mechanisms (Ginzburg & Zhelezniakov 1975) or plasma wave instabilities (Cheng & Ruderman 1977).…”
Section: Phase-dependent Intensity Modulationmentioning
confidence: 99%
“…1 of Karastergiou & Johnston (2007). A carefull recent study of the sign reversing circular polarisation is presented in Gangadhara (2010), Wang et al (2012), and Wang et al (2010). Moreover, Michel's fan beams were very elongated (∆θ ∼ 1 rad), and more complicated than the single-parameter conal beams, which seemed to be so well designed to match the imposing flaring polar tube.…”
Section: Introductionmentioning
confidence: 99%